Stališča mladostnikov do samomorilnega vedenja - Arnautovska, Urška (Psihološka obzorja (Ljubljana), 2008)
Throughout history, the social convictions and norms have influenced the recognition and presence of suicidal behaviour in different ways. However, previous research findings regarding the connection between suicidal behaviour and attitudes towards suicide have not arrived at a clear conclusion. The present research explores adolescents' attitudes toward suicide. The aim was to examine the relation between the permissive attitude toward suicide on one side and certain suicide risk factors and satisfaction in different domains of psychical functioning on the other side. Data was collecetd on 423 high school students in three Slovenian cities, chosen on the basis of different regional suicide rates, with an Attitudes towards suicide questionnaire ATTS, Psychological well-being scales PWBS, and questions about suicidal behaviour of adolescents and their surroundings. The results showed that the acceptance of suicide is proportional to the suicide rates of different regions. We concluded that permissive attitudes towards suicide could potentially lead to the increased risk of suicidal behaviour. Furthermore, the acceptance of suicide was, inter alia, significantly positively related to the self-reported probability of committing suicide, the presence of suicidal behaviour of the adolescent and his/her friends or other people he/she knows, while the connection with the subjective life satisfaction was negative. Considering the fact that there has been a trend of growing permissiveness towards suicide in society in the last few decades, the findings raise a question regarding the positive effects of such tolerance on suicide rates and support the justification of restrictive attitudes towards suicide as a protective factor of suicidal behaviour.
Keywords: mladostniki; stališča; samomori; samomorilno vedenje